Retracted: Evaluation of Effects of Soil pH Levels and Organic Matter Contents on Phytoaccumulation of Lead and Cadmium Heavy Metals by Imperata Cylindrica - Nimat, Abdulazeez; Anka, S.A.; Sanda, Aminu; Zauro, S.A. (Journal of Multidisciplinary Science: MIKAILALSYS, 2023)
Heavy metal contamination of soil pose risks and hazards to humans and the ecosystem through. Imperata cylindrica is a fast growing plant and often used for phytoremediation. The plant was tested in different growth media of spiked heavy metal, soil pH and organic matter contents for 60-day. After harvesting, the plant was washed, separated into roots and shoots. The soil samples were digested using 1.0g portion of dried the soil ,10.0cm3 of 1:1 HNO3: H2O, 5.0cm3 of HNO3, 1.0cm3 of H2O2, and 5.0cm3 of HCl while the plant samples were digested using 0.50g of the powdered sample, 5cm3 of HNO3 and 2cm3 HClO4. Prior to digestion, each sample were oven-dried at 70°C until it achieved a constant weight, grounded (using mortar and pestle) and milled (using a milling machine). Atomic absorption spectrophotometry was used to analyze the accumulation of cadmium, and lead in roots and shoot of the plant. Bioaccumulation factor (BF), biological accumulation coefficient (EC) and translocation factor (TF) was applied to evaluate the metal translocation ability in the plant. Between soil pH and soil organic matter, the highest total biomass of Cd was found in 300g of organic matter treatment (13.48 ± 2.69 mg/kg), while Pb in basic treatment was 18.09 ± 0.66 mg/kg. The result suggests that soil pH has most effect on Pb; while organic matter in Cd in the phytoaccumulation by Imperata cylindrica. The growth of phytoremediation plants like Imperata cylindrica should be encourage to neutralize the heavy metals pollution.